Smear negative pulmonary tuberculosis and infectivity - Thapa, B (International Journal of Infection and Microbiology, 2013)
DOI: http://dx.doi.org/10.3126/ijim.v2i3.8663 Int J Infect Microbiol 2013;2(3):68-69